For t=0
<span>Allan borrows--------------------------- > 1870 dollars
for t=6 years
</span>F1 = P*(1 +(r/m))^n
i=r/m
n=m*t---------- >1*6=6
we have
P1=1870
r=8%
m=1
t=6 years
F1 = 1870*(1 +(0.08/1))^6------------------ >2967.45 dollars
for t=2
Allan borrows--------------------------- > 1240 dollars
for t=6 years
F2 = P2*(1 +(r/m))^n
i=r/m
n=m*t---------- >1*4=4
we have
P2=1240
r=8%
m=1
t=4 years------------> (6-2)=4 years
F2 = 1240*(1 +(0.08/1))^4------------------ >1687 dollars
F1+F2=2967.45+1687=4654.45 dollars
the answer is 4654.45 dollars
The answer will be 90% of the people egeniring
I don’t understand you are asking
Ok what else about ms. palmer?
Answer:
y=2x-3
Explanation:
which equation represents the relationship between x and y shown in the table?
x | y
2 | 1
4 | 5
6 | 9
8 | 13
take a look at the values in the table one more,
we find the gradient of the line to be
G=y2-y1/(x2-x1)
G=13-1/(8-2)
slope/gradient=12/6
m=2
from equation of a line graph, we know
y=mx+c
m=gradient
c=intercept
y=vertical axis
x=a point on the horizontal axis
y=2x+c
when x=6, y=9
9=2(6)+C
c=-3
Therefore the equation becomes
y=2x-3
Step-by-step explanation: